Computer Simulation of a Hexagonal Assembly for a Branched Chain Glycolipid - T. Chong, Teoh; Heidelbergl, , Thorsten; A. Bryce, Richard (Malaysian Journal of Science, 2008)
Glycolipids are surfactants that assemble in ordered structures both in the presence and absence of a solvent, e.g. water. Branched chain glycosides with long chain length display stable columnar assemblies, which are commonly hexagonal packed. We here report on a molecular dynamics simulation study of a Guerbet-type maltoside involving a long symmetrically branched chain alcohol. A hexagonal columnar model-assembly involving 224 glycolipid and 560 water molecules with a total of almost 27,000 atoms was constructed and monitored over a period of 5 ns at 300 K using Amber. The simulation indicates stability for the hexagonal structure and classifies the water as bound water.